Landscape drivers of pests and pathogens abundance in arable crops. Issue 10 (29th August 2021) - Delaune, Thomas; Ouattara, Malick S.; Ballot, Rémy; Sausse, Christophe; Felix, Irène; Maupas, Fabienne; Chen, Mathilde; Morison, Muriel; Makowski, David; Barbu, Corentin
Abstract : Farmers' use of fungicides and insecticides constitutes a major threat to biodiversity that is also endangering agriculture itself. Landscapes could be designed to take advantage of the dependencies of pests, pathogens and their natural enemies on elements of the landscape. Yet the complexity of the interactions makes it difficult to establish general rules. In our study, we sought to characterize the impact of the landscape on pest and pathogen prevalence, taking into account both crop and semi‐natural areas. We drew on a nine‐year national survey of 30 major pests and pathogens of arable crops, distributed throughout the latitudes of metropolitan France. We performed binomial LASSO generalized linear regressions on the pest and pathogen prevalence as a function of the landscape composition in a total of 39 880 field × year × pest observation series. We observed a strong disequilibrium between the number of pests or pathogens favored (15) and disadvantaged (2) by the area of their host crop in the landscape during the previous growing season. The impact of the host crop area during the ongoing growing season was different on pests than on pathogens: the density of most pathogens increased (11 of 17, and no decreases) while the density of a small majority of pests decreased (7 of 13, and four increases). We also found that woodlands, scrublands, hedgerows and grasslands did not have a consistent effect on the studied spectrum of pests and pathogens. Although overall the estimated effect of the landscape is small compared to the effect of the climate, a territorial coordination that generally favors crop diversity but excludes a crop at risk in a given year might prove useful in reducing pesticide use. Short abstract We sought to identify general rules characterizing the impact of the landscape on the prevalence of pests and pathogens of arable crops. We showed that the host crop area is consistently correlated with increased pressure of the pests and pathogens the following growing season. Correlations of pests and pathogens with host crop areas in the same year or with semi‐natural components of the landscape (grasslands, hedgerows and forests) are less consistent and depend on the functional traits of the organisms involved.